The Influence of Animation Media In Understanding Fractions In Mathematics - Sari, Elok Fariha; Sukestiyarno, YL; Isnaeni, Wiwi; Yuwono, Agus (Universitas Negeri Semarang, 2024)
This research aims to determine the effect of animated video media in understanding fractions in mathematics subjects to improve elementary school students' learning outcomes. The type of research used was Quasi Experiment with Nonequivalent Control Group Design, namely research conducted in two classes, namely the experimental class and the control class. This research was conducted in class IV of the Pesantren Elementary School. The data collection techniques used were tests and observations. Data validation through content validity, instrument testing, reliability testing. Data analysis uses inferential statistical techniques through normality tests, homogeneity tests, and T tests. Based on the research results, the average learning outcomes test score before being given treatment (pretest) in the experimental class is 39.54, while the average learning outcomes test score after being given treatment (posttest) was 81.93. And the results of the hypothesis test show a sig (2-tailed) result of 0.000, where 0.000 < 0.05, so Ho is rejected, and Ha is accepted. This means that there is a difference in the use of animated video media in understanding fraction material in mathematics learning in class IV of the Semarang City Pesantren Elementary School between before being given treatment (pretest) and after being given treatment (posttest). So, there is an influence of animated video media in understanding fraction material in mathematics subjects to improve the learning outcomes of fourth grade elementary school students at the Semarang City Pesantren State Elementary School for the 2023/2024 academic year